The THE CONTRIBUTION OF PERCEIVED ORGANIZATIONAL SUPPORT TO EMPLOYEE WELL-BEING AMONG PRIVATE ELEMENTARY SCHOOL TEACHERS: Kontribusi Perceived Organizational Support Terhadap Employee Well-Being Pada Guru Sekolah Dasar Swasta - Amelia Fitar, Maia; Tuti Rahmi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Employee well-being play an essential role in is teacher performance and educational sustainability. However, it remains a challenge among private elementary school teachers due to higher job instability compared to public school teachers. This study aims to examine the contribution of perceived organizational support to employee well-being among private elementary school teachers in West Sumatra. A quantitative approach with correlation methods using simple linear regression was employed. Cluster sampling was aplied, with five regions as sample areas. A total of 395 private elementary school teachers in West Sumatra selected as sample areas. A total of 395 private elementary school teacher in West Sumatra participated. Data were collected using the Zheng Employee Well-Being Scale and the Eisenberger Perceived Organizational Support Scale, both of which have been adapted into Indonesian. The results indicate that perceived organizational support significantly and positively contributes to employee well-being (p<0,001). Furthermore, perceived organizational support accounted for 20,1% of employee well-being. These findings point to the importance of strengthening organizational support policies in private schools and provide empirical evidence of the of role of perceived organizational support in enchancing teacher well-being.